2022
DOI: 10.3390/jcm11216534
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a 6-Week Cycle of Nordic Walking Training on Vitamin 25(OH)D3, Calcium-Phosphate Metabolism and Muscle Damage in Multiple Myeloma Patients–Randomized Controlled Trial

Abstract: Introduction: Multiple myeloma (MM) is a hematological malignancy affecting older adults. One of the most common myeloma-defining events is the development of symptomatic lytic bone disease. The serum concentrations of calcium (Ca), inorganic phosphorus (P), and vitamin 25(OH)D3 in the serum reflect bone metabolism. An enzyme lactate dehydrogenase (LDH) is a marker of muscle damage, but its serum activity also has an important prognostic value in MM. Myoglobin (Mb) is a small protein present in muscles; its se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…On contrary, the proposed interventions improved the concentrations of some bone formation-related markers analyzed in this study. Previous publications on exercise interventions in patients with MM or pre mm conditions also did not show significant differences in weight and body composition [26][27][28].…”
Section: Discussionmentioning
confidence: 82%
“…On contrary, the proposed interventions improved the concentrations of some bone formation-related markers analyzed in this study. Previous publications on exercise interventions in patients with MM or pre mm conditions also did not show significant differences in weight and body composition [26][27][28].…”
Section: Discussionmentioning
confidence: 82%
“…Both studies [ 20 , 26 ], individualised the frequency of exercise according to the duration of treatment the women under study were undergoing, specifically according to the duration of chemotherapy, and supervision of the subjects was carried out weekly in much the same way in the two studies, through telephone calls or face-to-face consultation with a specialist. This type of exercise has been used by other researchers with the same objective and has produced results along the same lines as ours [ 28 ].…”
Section: Discussionmentioning
confidence: 96%
“…There is a clear predominance of aerobic exercise with intensities ranging from low-moderate to moderate-vigorous in the interventions performed, concluding that the interventions with the best results are those performed at moderate intensity. Donnelly et al [ 9 ], in addition to aerobic intervention (mainly walking) [ 28 ], chose to add strengthening exercises. Others such as Mizrahi et al [ 21 ] or Zhang et al [ 23 ] incorporated resistance exercise, as current guidelines recommend the inclusion of resistance training [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main groups of drugs used in treatment are alkylating agents, corticosteroids, immunomodulatory drugs and proteasome inhibitors 7 . The use of physiotherapy in patients with myeloma results in a reduction in perceived fatigue 8 as well as can affect patients’ functional ability 9 . In 2013, a study was conducted that found improvements in quality of life and strength after the intervention.…”
Section: Introductionmentioning
confidence: 99%
“…The therapy process included stretching, aerobic and resistance exercises and lasted for a total of 6 months 10 . Research by Czerwińska et al showed that for patients with MM, Nordic walking training is a safe form of physical activity, and could positively affect serum vitamin D concentration 9 , as well as disease-related blood parameters 11 .…”
Section: Introductionmentioning
confidence: 99%